2021
DOI: 10.1016/j.psj.2020.12.068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lysine biomass supplementation on growth performance and clinical indicators in broiler chickens

Abstract: Production of crystalline amino acids ( AA ) through microbial fermentation concomitantly provides an AA-enriched biomass that may serve as a cost-effective supplement for broiler chickens. We investigated the effects of feeding a fermentation biomass product containing approximately 62% Lys on growth performance, organ growth, and clinical outcomes of broilers. Beginning at 2 d post-hatch, a total of 360 Ross 308 chicks were randomly assigned to 1 of 5 treatments provided to 12 replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Hussain et al, (2018) demonstrated that a 1.30% digestible Lys level regimen with an optimal amino acid ratio may be employed to boost early development in native Aseel chickens. Jespersen et al, (2021) stated that 0.30% lysine biomass (LB) meals produced comparable overall (0-35 days body weight growth, and birds were heavier (P<0.001) than the other LB treatments. Pirzado et al, (2021) found that 12g/kg lysine levels in diet resulted in greater body weight increase.…”
Section: Results and Discussion 1-growth Performance The Effect Of Ly...mentioning
confidence: 99%
See 2 more Smart Citations
“…Hussain et al, (2018) demonstrated that a 1.30% digestible Lys level regimen with an optimal amino acid ratio may be employed to boost early development in native Aseel chickens. Jespersen et al, (2021) stated that 0.30% lysine biomass (LB) meals produced comparable overall (0-35 days body weight growth, and birds were heavier (P<0.001) than the other LB treatments. Pirzado et al, (2021) found that 12g/kg lysine levels in diet resulted in greater body weight increase.…”
Section: Results and Discussion 1-growth Performance The Effect Of Ly...mentioning
confidence: 99%
“…According to Jespersen et al (2021), the 0.30% lysine biomass (LB) and 0.90% LB groups showed a higher (P≤0.001) total FCR than the negative control (NC). Pirzado et al, (2021) demonstrated that a lysine content of 12g/kg in diet enhanced feed efficiency (FE).…”
Section: -Feed Conversion Ratio and Daily Feed Intake: Effect Of Lysi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Bouyeh [ 41 ] reported a reduction in weight gain when feeding broiler chickens with a Lys content that was 40% greater than the NRC recommendation (1.54% and 1.40% during the starter and growing periods, respectively). Recently, Jespersen et al [ 42 ] observed that doubling the Lys content at 2.13% and 1.95% in the starter and grower diets compared to the NRC recommendation slowed the growth rate of broiler chickens. They attributed this decrease in the growth performance of those birds to a deficiency of arginine [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, serum proline and lysine were lowest in the LPR group, consistently lower than in the LPM group. The lower serum proline and lysine may explain why the growth performance was the weakest in the LPR group since lysine ( Jespersen et al, 2021 ) is vital in promoting poultry growth ( Lee et al, 2020 ). Our data demonstrated that the proline might be essential in promoting growth in goslings fed with low-protein diets.…”
Section: Discussionmentioning
confidence: 99%